Hypoglycemia symptoms and awareness of hypoglycemia in type 1 diabetes mellitus : cross-cultural adaptation and validation of the Portuguese version of three questionnaires and evaluation of its risk factors - Stefenon, Paula (2020)
Background: To adapt and validate the Clarke and Gold questionnaires and the Edinburgh Hypoglycemia Symptom Scale (EHSS) to Brazilian Portuguese and to determine the prevalence and risk factors associated with impaired awareness of hypoglycemia (IAH) in patients with type 1 diabetes mellitus (T1DM). Methods: The process of translation, cultural adaptation, and validation of the questionnaires followed the recommendations of the International Society for Pharmacoeconomics and Outcomes Research (ISPOR)-Task Force for Translation and Cultural Adaptation. Patients with T1DM for a minimum of 12 months, aged 18 years or older, and with Brazilian nationality were selected to participate. Results: A total of 123 patients were enrolled. The Clarke and Gold questionnaires as well as the EHSS exhibited adequate internal consistency, test–retest reliability, and convergent validity. The prevalence of IAH was 38.3% with the Clarke questionnaire and 25.2% with the Gold questionnaire. The prevalence increased with longer duration of diabetes, lower HbA1c, and lower eGFR. Conclusions: The validation and cross-cultural adaptation of the proposed questionnaires to Brazilian Portuguese were adequate. In this sample of T1DM, the prevalence of IAH was high and associated with a longer duration of T1DM, lower HbA1C and lower eGFR.